Taking Stock: Equity‐Based Compensation and the Evolution of Managerial Ownership - Ofek, Eli; Yermack, David (Journal of Finance, 2000)
We investigate the impact of stock‐based compensation on managerial ownership. We find that equity compensation succeeds in increasing incentives of lower‐ownership managers, but higher‐ownership managers negate much of its impact by selling previously owned shares. When executives exercise options to acquire stock, nearly all of the shares are sold. Our results illuminate dynamic aspects of managerial ownership arising from divergent goals of boards of directors, who use equity compensation for incentives, and managers, who respond by selling shares for diversification. The findings cast doubt on the frequent and important theoretical assumption that managers cannot hedge the risks of these awards.